Religious beliefs, coping skills and responsibility to family as factors protecting against deliberate self-harm - Kannan, K.; Pillai, S.K.; Gill, J.S.; Hui, K.O.; Swami, V. (Sa Medical Assoc Health & Medical Publ Group, 2010)
Background. Deliberate self-harm (DSH) ranges from behaviours aiming to communicate distress or relieve tension, but where suicide is not intended, to suicide. Not all individuals are prone to DSH, which suggests that there are Factors that protect against it. Identifying these could play an important role in the management and prevention of DSH. Objectives. This study examined whether religious beliefs, coping skills and responsibility to family serve as factors protecting against DSH in Kota Kinabalu, Sabah, Malaysia. Method. A cross-sectional comparative study assessed DSH patients consecutively admitted or directly referred to Queen Elizabeth General Hospital and Hospital Mesra Bukit Padang during the period December 2006 - April 2007. DSH patients (N=42) were matched with controls (N=42) for gender, age, religion, race, occupation and marital status. The DSH and control groups were compared using psychosocial tests that assess coping skills, religious beliefs and responsibility to family. Results. There were significant differences in religious beliefs (p=0.01) and responsibility to family (p=0.03) between the DSH patients and the control group. There were also significant differences in coping skills, DSH patients tending to use emotion-orientated coping (p=0.01) as opposed to task- and avoidance-orientated coping. Conclusion. Consistent with international studies, coping skills (i.e. task-orientated skills), religious beliefs and responsibility to family were more evident in patients who did not attempt DSH than in those who did. These findings imply that treating DSH should not start only at the point of contact. Protective factors such as religious beliefs, responsibility to family and coping strategies can be inculcated from a very young age. However, caution is required in generalising the results owing to limitations of the study. Further extensive research on religious and psychotherapeutic interventions and prospective studies on protective factors will be helpful.